Econometric Analysis of Investment and Internal Finance under Asymmetric Information: A Case Study of Manufacturing companies of Pakistan (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2017)
The current research investigates Econometric Analysis of Investment and Internal Finance under Asymmetric Information: A Case Study of Manufacturing companies ofPakistan.  This study also aims to explore the relationship between internal finance and corporate investment outlays of Pakistani manufacturing firms in the presence of asymmetric information in the capital market. The fixed effect model has been employed on a sample of conveniently selected 272 listed manufacturing firms (with 2720 observations) over the period 2001 to 2010. Two different proxies of asymmetric information (i.e. Firm size & age) are used. Based on each of these two measures the sample is split into two subsamples (i.e. Small & large size and young & old firms respectively). Firms with small size and young firms are facing the asymmetric information while the other two subsamples are not considered so. The results based on all of the two measures indicate that there is a statistically significant and positive relationship between investment and internal finance or the cash flows. The investment of those firms where there is asymmetric information (i.e. small size, and young firms) such firms are more sensitive to the changes in their internal finance.